The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1093/cvr/cvw184
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide and natriuretic peptide receptor B signalling inhibits cardiac sympathetic neurotransmission and autonomic function

Abstract: AimsB-type natriuretic peptide (BNP)–natriuretic peptide receptor A (NPR-A) receptor signalling inhibits cardiac sympathetic neurotransmission, although C-type natriuretic peptide (CNP) is the predominant neuropeptide of the nervous system with expression in the heart and vasculature. We hypothesized that CNP acts similarly to BNP, and that transgenic rats (TGRs) with neuron-specific overexpression of a dominant negative NPR-B receptor would develop heightened sympathetic drive.Methods and resultsMean arterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
0
24
0
1
Order By: Relevance
“…Upon stretch of the cardiac wall, ANP and BNP are released into the circulation, inducing increased renal excretion of sodium and water, increased vascular permeability and vasodilation, leading to a reduction in systemic blood pressure (Curry 2005;Houben et al 2005), while CNP induces vasodilation (Wei et al 1993). Recent research has also shown BNP and CNP regulate cardiovascular function by direct inhibition of cardiac sympathetic neurotransmission (Buttgereit et al 2016;Li et al 2015). Identification of NP production and NPR expression in a broad range of tissues suggests this system has biological effects beyond the regulation of kidney and cardiovascular functions.…”
Section: Introductionmentioning
confidence: 99%
“…Upon stretch of the cardiac wall, ANP and BNP are released into the circulation, inducing increased renal excretion of sodium and water, increased vascular permeability and vasodilation, leading to a reduction in systemic blood pressure (Curry 2005;Houben et al 2005), while CNP induces vasodilation (Wei et al 1993). Recent research has also shown BNP and CNP regulate cardiovascular function by direct inhibition of cardiac sympathetic neurotransmission (Buttgereit et al 2016;Li et al 2015). Identification of NP production and NPR expression in a broad range of tissues suggests this system has biological effects beyond the regulation of kidney and cardiovascular functions.…”
Section: Introductionmentioning
confidence: 99%
“…The slow pace of developing novel HF therapies available to patients highlights the need for novel pathways that have therapeutic potential, which may extend beyond HF to other cardiovascular diseases. The present study by Buttgereit et al 4 and that of Li et al 3 suggest a back to the 'A B C's' is needed on NP signalling in physiologic and pathophysiologic conditions, and highlights the need for further research in this area.…”
mentioning
confidence: 48%
“…At doses in the pathophysiologic range, CNP does not have diuretic or natriuretic effects in normal patients 8,9 , while other studies also suggest that vasodepressor and natriuretic activity of CNP is weaker than ANP. 10 These studies did not assess biomarkers of sympathetic neurotransmission to determine whether CNP-modulated sympathetic signalling, however, they emphasize that the primary action of CNP may be geared towards preventing sympathetic neuron hyperactivity as suggested by this study and others, 4,11 and to facilitate vagal neurotransmission as previously shown. 12 Although elucidating key mechanisms for CNP-mediated modulation of sympathetic neurotransmission furthers our understanding of NPs as a family, some important considerations are raised regarding what occurs in pathology.…”
mentioning
confidence: 75%
See 2 more Smart Citations